2011
DOI: 10.1103/physreve.83.031920
|View full text |Cite
|
Sign up to set email alerts
|

Collective behavior of brain tumor cells: The role of hypoxia

Abstract: We consider emergent collective behavior of a multicellular biological system. Specifically, we investigate the role of hypoxia (lack of oxygen) in migration of brain tumor cells. We performed two series of cell migration experiments. In the first set of experiments, cell migration away from a tumor spheroid was investigated. The second set of experiments was performed in a typical wound-healing geometry: Cells were placed on a substrate, a scratch was made, and cell migration into the gap was investigated. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 47 publications
3
96
1
4
Order By: Relevance
“…Why would a metastatic cell activate an anaerobic metabolic pathway and bypass the mitochondria? One answer seems to be that the interior of a cancer tumor is very acidic and hypoxic (7)(8)(9). In this highly stressful anaerobic microenvironment, fitness is conferred by the Warburg cycle despite its low thermodynamic efficiency.…”
mentioning
confidence: 99%
“…Why would a metastatic cell activate an anaerobic metabolic pathway and bypass the mitochondria? One answer seems to be that the interior of a cancer tumor is very acidic and hypoxic (7)(8)(9). In this highly stressful anaerobic microenvironment, fitness is conferred by the Warburg cycle despite its low thermodynamic efficiency.…”
mentioning
confidence: 99%
“…Previously, we demonstrated that hypoxia contributes to glioma migration by decreasing cell-to-cell adhesion rather than increasing individual cell motility [25]. It was recently reported that hypoxia promotes hypoxia inducible factor 1α (HIF-1α) -mediated up-regulation of miR-9 in pulmonary artery smooth muscle cells, however the effect of hypoxia upon miR-9 in tumor has yet to be investigated [11].…”
Section: Resultsmentioning
confidence: 99%
“…The periodic boundary conditions were used along the vertical direction, whereas open boundaries were used for the horizontal direction, which represents the direction of tumor invasion. Our approach is similar to the scenario when Bindsschadler and McGrath [67] and Khain et al [68] used parallel strips surrounded by cell-cultured strips made with microfabricated stencils for observation of collective cell migration. For the sake of simplification, we assumed that an initial tumor seed is located at x' = 0 and y' = 0.5 and spreads isotropically.…”
Section: Model With Nondimensionalization and Parameterizationmentioning
confidence: 86%